2011
DOI: 10.1177/1460458211414843
|View full text |Cite
|
Sign up to set email alerts
|

Exploring digital divides: An examination of eHealth technology use in health information seeking, communication and personal health information management in the USA

Abstract: Recent government initiatives to deploy health information technology in the USA, coupled with a growing body of scholarly evidence linking online heath information and positive health-related behaviors, indicate a widespread belief that access to health information and health information technologies can help reduce healthcare inequalities. However, it is less clear whether the benefits of greater access to online health information and health information technologies is equitably distributed across populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
153
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(180 citation statements)
references
References 56 publications
11
153
1
2
Order By: Relevance
“…HIT engagement is more common among certain demographic groups. High educational attainment [8][9][10], female gender [7,9,11], individuals with chronic health conditions such as cancer or caregivers for those with a chronic condition [12][13][14], and higher income [15] were predictors of HIT engagement. Older adults (65 years of age and older) are less likely to engage in HIT activities [15][16][17][18], including accessing personal health records electronically [16].…”
Section: Introductionmentioning
confidence: 99%
“…HIT engagement is more common among certain demographic groups. High educational attainment [8][9][10], female gender [7,9,11], individuals with chronic health conditions such as cancer or caregivers for those with a chronic condition [12][13][14], and higher income [15] were predictors of HIT engagement. Older adults (65 years of age and older) are less likely to engage in HIT activities [15][16][17][18], including accessing personal health records electronically [16].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the Health Information and National Trends Survey (HINTS) in the United States and an Australian survey show the public to be increasingly engaged with online health information (18)(19)(20)(21). In the cancer field, use of online information by cancer survivors is well documented (22)(23)(24)(25)(26), and the Internet is being used as a resource for cancer-related information in the general population (27).…”
Section: Introductionmentioning
confidence: 99%
“…[5,35] On the positive side some studies point that use OHS increases the odds for monitoring a health problem in time due to delayed face-to-face appointments or timely access to the results of lab tests. [10,18,30,36,37] In a recent study among small samples of white females with diabetes, for example participants reported greater self-efficacy for managing their disease [23] the benefits of communicating with health care providers and/or website moderators to receive feedback and social support and tracking (e.g., graphical displays of uploaded personal data) were shown to particularly useful for self-management support but less so for improvements in medication adherence, biological outcomes and health care utilization. [38] On the negative side some studies suggest that use of OHS may fall behind the intended purposes and fail in providing effective health services.…”
Section: Introductionmentioning
confidence: 99%
“…Health behavior according to Bandura's self-efficacy hypothesis [12] can be promoted by social-cognitive means available ion OHI [13,14] and according to the Media Dependency Hypothesis, can be further amplified by the use of OHS [10,15] increasing the advantages of self-management practices in health [16] and significant effects that OHS or lack of, may have on CD patients [4,[17][18][19] have been reported especially among patients diagnosed with cancer, [20,21] heart condition, [22] diabetes [23] and other long-term conditions. [24,25] Use of OHS is indeed considered as significant means for self-management because it facilitates treatment and follow ups and prevents unnecessary health complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation